Home nursing assistance: perception of the family - Lorita Marlena Freitag Pagliuca; Rosane Arruda Dantas; Paulo César de Sousa Batista (Rev Rene)
It is important to get to know the perception of the relatives who are responsible for patients in home care. Thus, the objective of this research was to characterize clients and their relatives who use the home care system and to identify the factors which infl uence such clients’ level of satisfaction. This cross-sectional descriptive study aims to picture the satisfaction of 21 relatives responsible for patients attended by a home medical care company in the private health system in Fortaleza, Brazil. Among the relatives, the female gender predominated (28.5%), with either daughters (28.5%) or wives (28.5%), The ones who had completed higher education (52.4%) and who were between 28 and 38 years of age (33.3%). Among the patients, the male gender was predominant (52%), aged between 71 and 93 years of age (11%) The ones who had fi nished secondary education (38%) and who were between one and two years of medical care (57.1%). Among the relatives, 62% were pleased with the service. Restrictions referred to time, number of visits and the professionals’ behavior. Home care reveals to be a good option when indicated for the case.